1985
DOI: 10.1111/j.1365-2125.1985.tb02649.x
|View full text |Cite
|
Sign up to set email alerts
|

The plasma noradrenaline and growth hormone response to alpha‐ methyldopa and clonidine in hypertensive subjects.

Abstract: 1 The mechanism of the antihypertensive effect of ot-methyldopa was compared with clonidine by administering equipotent single doses of clonidine (0.2 mg) and amethyldopa (750 mg) to nine hypertensive patients. Plasma noradrenaline was followed for 8 h thereafter as an index of peripheral sympathetic activity. 2 a-Methyldopa and clonidine produced the same hypotensive response at 6 and 8 h after dosing with a similar fall in plasma noradrenaline levels at these times. 3 Linear regression analysis between the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

1986
1986
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
2
3
1
Order By: Relevance
“…In our experimental conditions, clonidine did not decrease the urinary excretion of NA or NMN. Such a result differs from other studies reporting that, in humans, clonidine decreased plasma NA (Guthrie & Kotchen 1983;Struthers et al 1985;Cubeddu et al 1986) and A (Chodakowska et af. 1987).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In our experimental conditions, clonidine did not decrease the urinary excretion of NA or NMN. Such a result differs from other studies reporting that, in humans, clonidine decreased plasma NA (Guthrie & Kotchen 1983;Struthers et al 1985;Cubeddu et al 1986) and A (Chodakowska et af. 1987).…”
Section: Discussioncontrasting
confidence: 86%
“…(1 987); moreover after cessation of chronic treatment, an overshoot in heart (HR) was observed by Van Zwieten et al (1 986) and Atkinson et al (1986) but not by Jarrott and Lewis (1 987). In hypertensive subjects the plasma noradrenaline (NA) concentration, used as an index of the peripheral sympathetic activity, was reported to be decreased by Guthrie and Kotchen (1983), Struthers et al (1985) and (1 987).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study supplement the findings of others that clonidine administration lowers plasma noradrenaline (Metz and Halter, 1980;Manhem et al, 1982;Siever et al, 1984;Struthers et al, 1985;Nutt and Molyneaux, 1986;Hoehe et al, 1988). Our study indicates that clonidine also lowers plasma DHPG levels, 1 h after administration.…”
Section: Discussionsupporting
confidence: 91%
“…An implication of these findings and those of Struthers et al (1985) is that if blunting of growth hormone responses is confirmed as a reliable marker for endogenous depression, as it has been claimed (Checkley et ul., 1985), then this blunting should not be taken as evidence of a generalized adrenergic defect. Rather it would appear necessary to study further local hypothalamic and pituitary factors influencing growth hormone release before a proper characterization of the deficit in depression can be offered.…”
Section: Discussionsupporting
confidence: 62%
“…Clonidine also causes significant GH increases in normal subjects {Cella, Morgese, Mantegazza and Muller 1984;Alba-Roth, Losa, Spiess, Schopohl, Midler and von Werder 1989) probably increasing the endogenous secretion of GHreleasing hormone (GHRH) by the hypothalamus. Central alpha-2 adrenergic receptor function in patients with essential hypertension indirectly studied evaluating the effects of clonidine on GH secretion was reported either to be impaired (Barbieri, Ferrari, Caldara and Curtarelli 1980;Struthers, Brown, Adams and Dollery 1985) or normal {Bramnert and Hockfelt 1984;Slowinska-Srzednicka, Zgliczynski, Wierzbiki, Soszyriski and Jeske 1988) in hypertensive patients with respect to normal controls. However, in hypertensive patients the effects of clonidine on GH secretion were never compared with those of GHRH.…”
Section: Introductionmentioning
confidence: 99%